Could incommensurability in sulfosalts be more common than thought? The case of meneghinite, CuPb13Sb7S24. Issue 3 (12th May 2017) - Bindi, Luca; Petříček, Václav; Biagioni, Cristian; Plášil, Jakub; Moëlo, Yves
Abstract : The crystal structure of the mineral meneghinite, CuPb13 Sb7 S24, has been solved and refined as an incommensurate structure from X‐ray single‐crystal diffraction data in four‐dimensional superspace. The very small departure from the commensurate value of the modulation raises the question of whether incommensurability in sulfosalts could be much more frequent than previously thought. Abstract : The structure of meneghinite (CuPb13 Sb7 S24 ), from the Bottino mine in the Apuan Alps (Italy), has been solved and refined as an incommensurate structure in four‐dimensional superspace. The structure is orthorhombic, superspace group Pnma (0β0)00 s, cell parameters a = 24.0549 (3), b = 4.1291 (6), c = 11.3361 (16) Å, modulation vectorq = 0.5433 (4)b* . The structure was refined from 6604 reflections to a final R = 0.0479. The model includes modulation of both atomic positions and displacement parameters, as well as occupational waves. The driving forces stabilizing the modulated structure of meneghinite are linked to the occupation modulation of Cu and some of the Pb atoms. As a consequence of the Cu/[] and Pb/Sb modulations, three‐ to sevenfold coordinations of the M cations (Pb/Sb) occur in different parts of the structure. The almost bimodal distribution of the occupation of Cu/[] and Pb/Sb at M 5 conforms with the coupled substitution Sb 3+ + [] → Pb 2+ + Cu +, thus corroborating the hypothesis deduced previously for the incorporation of copper in the meneghinite structure. The very small departure (∼0.54 versus 0.50) from the commensurate value of the modulation raises the question of whether other sulfosalts considered superstructures have been properly described, and, in this light, if incommensurate modulation in sulfosalts could be much more common than thought.